The New World species of Leucospis Fabricius, 1775 (Hymenoptera, Chalcidoidea, Leucospidae): an update of Bouček’s revision with description of two new species from Brazil - Lima, Alessandro Rodrigues; Dias, Priscila Guimarães (Zootaxa, 2018)
The revision of Leucospis Fabricius (Hymenoptera: Leucospidae) by Bouček (1974a) is updated for the New World species based on material deposited in Brazilian collections. We provide a key to the New World species including all species described after Bouček, describe two new Brazilian species, Leucospis copepucu sp. nov. and L. muru sp. nov. describe the male of Leucospis opalescens Weld, 1922, and provide diagnoses and illustrations for ten other Brazilian species and one Argentinian species and comments on new geographic records for Brazilian species, with maps.